Experiences of adolescents and parents on the mental health management of depression in adolescents, North West province, South Africa - Precious C. Chukwuere; Leepile A. Sehularo; Mofatiki E. Manyedi (AOSIS, 2022)
Background: Living with or managing an adolescent suffering from depression predisposes the adolescent and parents to various experiences, considering the multifactorial nature of depression and associated symptoms. Objective: This study explored and described the experiences of adolescents and their parents on the mental health management of depression in the North West province (NWP), South Africa. Method: A qualitative, exploratory, descriptive, contextual research design was adopted. Data was collect from two mental health care institutions and two mental health care units attached to two general hospitals in the NWP, SA. Thirty-two participants (18 adolescents and 14 parents) were purposefully selected for the study. Data were collected through individual interviews and analysed using Tesch's open-coding method to generate themes and categories which were presented with the concurrent support of participants direct quotations. Results: The study revealed that the experiences of adolescents with depression and their parents taking care of them at homes include the following: emotional distress, poor coping mechanisms, financial burden, repeated suicidal attempts, negative attitudes from support systems and withdrawal behaviours. Appropriate therapeutic environments, ongoing monitoring by mental healthcare practitioners and adequate support systems were suggested by participants as management approaches that could enhance the recovery of adolescents from depression. Conclusion: The findings revealed the devastating experiences of adolescents with depression and their parents taking care of them in their various homes which confirms the dire need for attention on the plights of these groups in order to facilitate adolescents' recovery and strengthen the adolescents' and parents' coping mechanisms for a healthier family.